Federalismo fiscal: uma análise das relações intergovernamentais quanto ao atendimento das demandas sociais - o caso brasileiro - Milward, Julianne Alvim (2003)
This paper analyzes the relations between governmental Brazilian spheres, regarding to the provisions of the social demands. The focus of the study inhabits in the relations that result in negative externalities, meaning losses for collective welfare, in discordance with the pretensions of the new Constitution, promulgated in 1988. The investigate of the intergovernmental relations is carried through in the perspective of internalization institutions to the model of analysis, promoting a better understanding about the behaviors adopted for the federative units and therefore its results in the politic, economic and social scenarios, in function of the federative game current.